Artemin Promotes the Migration and Invasion of Cervical Cancer Cells through AKT/mTORC1 Signaling. (26th November 2022) - Zhu, Mengjing; Zhou, Ling; Fu, Jian; Wang, Yijin; Xu, Xiaofeng; Wu, Jun; Kong, Xiangyi; Li, Jian; Zhou, Zhe; Zhou, Huaijun
Abstract : Background . The neurotrophic factor Artemin (ARTN) is involved in tumor proliferation and metastasis. Nonetheless, ARTN's significance in cervical cancer (CC) has not been studied. In our study, we propose to investigate the biological function of ARTN in CC as well as its particular regulatory mechanism. Methods . Immunohistochemistry (IHC) was used to examine the degree of ARTN protein expression in CC patient tissue. Real-time PCR and Western blotting were performed to reveal related genes' levels in CC cells. The CCK-8 test, the colony formation assay, the wound-healing assay, and the transwell assay were utilized to determine the proliferation, migration, and invasion capabilities, respectively. To generate lung metastasis models, stable ARTN-expressing SiHa cells were injected into the caudal tail vein of mice. IHC was used to examine the protein levels in CC mice model tissues. Results . ARTN was overexpressed in CC tissues relative to normal cervical tissues and linked positively with lymph node metastases (P = 0.012 ) and recurrence (P = 0.015 ) in CC patients. In vitro, ARTN overexpression promoted the proliferation, invasion, and migration of CC cells. In contrast, the consequences of depleting endogenous ARTN were the opposite. Moreover, overexpression of ARTN increased lung metastasis of CC cells in vivo and shortened the lifespan of mice models. In addition, ARTN overexpression significantly enhanced AKT phosphorylation on Ser473 and mTOR phosphorylation on Ser2448 and promoted the epithelial-mesenchymal transition (EMT) cascade. In addition, rapamycin, a selective inhibitor of mTORC1, might rescue the EMT phenotype caused by ARTN. Conclusion . Our findings suggested that ARTN may enhance CC metastasis through the AKT/mTORC1 pathway. ARTN is anticipated to be a novel potential therapeutic target for the treatment of CC metastases.